Soil Nematodes as a Means of Conservation of Soil Predatory Mites for Biocontrol - Diana Rueda-Ramírez; Eric Palevsky; Liliane Ruess (Agronomy, 2022)
Numerous lab and field studies have reported the potential of soil predatory mites for the biological control of plant-parasitic nematodes and arthropods pests. Most of these studies have utilized biocontrol agents in augmentative releases, essentially controlling the pest with the released predators. While this may be a valid approach, we hypothesize that conservation of soil mite predators with available, suitable, and accessible free-living nematodes as prey, will provide better agricultural ecosystem performance and long-range sustainability. In this manuscript, we review the relevant studies on soil predatory mite–nematode interactions and highlight their potential for conservation biological control of soil-borne pests. Additionally, we emphasize the importance of implementing environmentally sound soil management practices for the sustainability and conservation of functional soil food webs.